2021
DOI: 10.3389/frsus.2021.681690
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Selection of Suitable Waste to Energy Technologies for a Sustainable Municipal Solid Waste Management System

Abstract: Municipal solid waste (MSW) generation has been escalated at a global scale and poses drastic impacts on the environment along with many socio-economic problems. Waste to energy (WtE) technologies have been recognized to convert MSW into useful energy and minimize the problems related to it. This study reviewed different WtE technologies according to the conversion pathways, end-products, and their applications, and assessed statistical values of these technologies based on six different factors, viz., environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 72 publications
(120 reference statements)
1
25
0
Order By: Relevance
“…The finding is similar with that of Kurbatov and Abu-Qdais [62], who reported that skills availability for landfill gas received the highest rank in Moscow. Incineration ranked second, which is consistent with the analysis of Farooq et al [63], who suggest that the low level of labour skills required for incineration makes it an ideal choice for developing countries like Ghana. The WtE technology with the preferred least capital cost was aerobic digestion, followed by landfill gas.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The finding is similar with that of Kurbatov and Abu-Qdais [62], who reported that skills availability for landfill gas received the highest rank in Moscow. Incineration ranked second, which is consistent with the analysis of Farooq et al [63], who suggest that the low level of labour skills required for incineration makes it an ideal choice for developing countries like Ghana. The WtE technology with the preferred least capital cost was aerobic digestion, followed by landfill gas.…”
Section: Resultssupporting
confidence: 87%
“…In Ghana, the grid availability is more efficient in urban than in rural areas, making it easier to transmit the electricity produced by the incineration plant. On the other hand, biochemical technologies, such as anaerobic digestion, which are suitable for rural areas (e.g., [63]) with inadequate grid availability, can make energy delivery very challenging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mir [48] aver that the population must accept a waste management system to be effective, and [49] underscores the importance of ensuring a higher standard of living for future generations, simply defined as sustainability. Hence a solid waste management system must be socially acceptable, economically viable, and environmentally efficient to be sustainable [50].…”
Section: Waste Management Practicesmentioning
confidence: 99%